2020
DOI: 10.1177/1369433220964375
|View full text |Cite
|
Sign up to set email alerts
|

A distance coefficient-multi objective information fusion algorithm for optimal sensor placement in structural health monitoring

Abstract: Optimal sensor placement (OSP) plays a key role in the construction and implementation of an effective structural health monitoring system (SHM). In this study, a novel and effective method named the distance coefficient-multi objective information fusion algorithm (D-MOIF), which is different from the conventional method and easier to be implemented, is developed to select the best sensor location for large-scale structures. An integrated information matrix including mode independence, damage sensitivity and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 29 publications
0
4
0
Order By: Relevance
“…Te concrete damaged plasticity (CDP) model proposed by Lee and Fenves [53] is adopted for the dam body. Te sensor layout scheme is designed using the normal cloud mutation-shufed frog leaping algorithm (NCM-SFLA) proposed by Cao et al [54]. A sensor system consisting of 32 single-axis acceleration sensors (the test direction is along the river) is also integrated, as shown in Figure 5.…”
Section: Design Of Source and Target Domainsmentioning
confidence: 99%
“…Te concrete damaged plasticity (CDP) model proposed by Lee and Fenves [53] is adopted for the dam body. Te sensor layout scheme is designed using the normal cloud mutation-shufed frog leaping algorithm (NCM-SFLA) proposed by Cao et al [54]. A sensor system consisting of 32 single-axis acceleration sensors (the test direction is along the river) is also integrated, as shown in Figure 5.…”
Section: Design Of Source and Target Domainsmentioning
confidence: 99%
“…where Q is an orthonormal matrix and Φ is the mode shape matrix. This metric has a few drawbacks: i) it might choose sensor locations with less energy content, just like KE, what can leave sensing incomplete and bring vulnerability in noisy conditions (Cao et al [2020]), ii) it presented poor results under conditions of uncertainty (Kammer [1992]).…”
Section: Modal Metrics In Structural Health Monitoringmentioning
confidence: 99%
“…The first using FIM and MSI at the same time, finding excellent results, iv) Cao et al [2020]: proposed a method named distance coefficient-multi-objective information fusion algorithm (D-MOIF) and two objective functions based on other metrics. The author was the first to study SPO in a more complex structure, v) Zhou et al [2021]: showed that the Multi-objective FA obtained better results than the NSGA-II, and vi) Colombo et al [2022]: proposed a statistical methodology that evaluated the positioning of sensors together with the damage identification.…”
Section: Introductionmentioning
confidence: 99%
“…With the development of intelligent technology, the methods of intelligent optimization algorithm, multidimensional sensor parameter fusion algorithm and multi-optimization algorithm cross fusion have been used for sensor arrangement optimization. For example, the Euclidean distance derived from analytic geometry by Cao et al [33] based on the principle of information entropy, constructed an optimized objective function and proposed a distance coefficient-multi-objective information fusion algorithm. Niu et al [34] combined QR decomposition method and genetic algorithm to realize the optimal arrangement of hydraulic structure health monitoring sensors.…”
Section: Introductionmentioning
confidence: 99%